Architecture of the Distal Piedmont‐Ligurian Rifted Margin in NW Italy: Hints for a Flip of the Rift System Polarity. Issue 11 (4th November 2017) - Decarlis, Alessandro; Beltrando, Marco; Manatschal, Gianreto; Ferrando, Simona; Carosi, Rodolfo
Abstract: The Alpine Tethys rifted margins were generated by a Mesozoic polyphase magma‐poor rifting leading to the opening of the Piedmont‐Ligurian "Ocean." This latter developed through different phases of rifting that terminated with the exhumation of subcontinental mantle along an extensional detachment system. At the onset of simple shear detachment faulting, two margin types were generated: an upper and a lower plate corresponding to the hanging wall and footwall of the final detachment system, respectively. The two margin architectures were markedly different and characterized by a specific asymmetry. In this study the detailed analysis of the Adriatic margin, exposed in the Serie dei Laghi, Ivrea‐Verbano, and Canavese Zone, enabled to recognize the diagnostic elements of an upper plate rifted margin. This thesis contrasts with the classic interpretation of the Southalpine units, previously compared with the adjacent fossil margin preserved in the Austroalpine nappes and considered as part of a lower plate. The proposed scenario suggests the segmentation and flip of the Alpine rifting system along strike and the passage from a lower to an upper plate. Following this interpretation, the European and Southern Adria margins are coevally developed upper plate margins, respectively resting NE and SW of a major transform zone that accommodates a flip in the polarity of the rift system. This new explanation has important implications for the study of the pre‐Alpine rift‐related structures, for the comprehension of their role during the reactivation of the margin and for the paleogeographic evolution of the Alpine orogen. Key Points: The Adriatic Jurassic rifted margin preserved in the Alps is related to an upper plate geometry The Jurassic Alpine rifting system was characterized by a major rift‐flip zone reactivated during the convergence phases of the orogeny